The causes for the foundation of the Diocese of Zvečan - Janjić, Dragana J. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
The short duration of the Diocese of Zvečan is to be explained with economic and political circumstances in Serbia, first of all with the development of mining, which doesn’t mean that other reasons of political nature, as conquests of king Milutin, didn’t have their influence. As strategically important stronghold, in the context of economic strengthening and long-lasting conflict between kings Dragutin and Milutin, the transfer of pontifical center in the fortified city of Zvečan does nod exclude the possibility that the nearness of the mine of Trepča and sudden growth of mining exploatation and trade, also meant that hierarch of Zvečan became Milutin’s man of trust in supervising and protection of king’s material resources